2017
DOI: 10.1556/004.2017.006
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of fetal thoracic aortic diameter measurement in the prediction of birth weight in Holstein-Friesian cows — Short communication

Abstract: Transabdominal ultrasonography has been shown to be a useful and reliable method for assessing fetal well-being in horses and cattle. To test the applicability of fetal aortic diameter measurement in cattle, 44 late-term pregnant cows and heifers were examined 21 to 0 days prior to calving. Mean fetal aortic diameter was 2.07 ± 0.14 cm and mean fetal heart rate (FHR) was 109 ± 17 bpm. Three dead calves were dissected and their aortic diameter was measured in a water bath. The mean birth weight (n = 44) was 39.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Vincze et al [40] measured the aortic diameter as 2.07 ± 0.14 cm by transabdominal ultrasonography and they found that there was a statistically significantly negative correlation (r = -0.41, p = 0.012) between the foetal heart weight and the foetal aortic diameter in 44 cattle foetuses in the late period of pregnancy. In the study conducted, it was determined that there was a statistically significantly positive correlation (r = 0.801, p < 0.01) between the foetal heart weight and the foetal aortic diameter in cattle foetuses.…”
Section: Statisticalmentioning
confidence: 99%
“…Vincze et al [40] measured the aortic diameter as 2.07 ± 0.14 cm by transabdominal ultrasonography and they found that there was a statistically significantly negative correlation (r = -0.41, p = 0.012) between the foetal heart weight and the foetal aortic diameter in 44 cattle foetuses in the late period of pregnancy. In the study conducted, it was determined that there was a statistically significantly positive correlation (r = 0.801, p < 0.01) between the foetal heart weight and the foetal aortic diameter in cattle foetuses.…”
Section: Statisticalmentioning
confidence: 99%